Enhancing green ports in Dar es Salaam Port: facility optimization for emission reduction through Mamdani and Sugeno Fuzzy inference systems - Kunambi, Majid Mohammed; Zheng, Hongxing (Frontiers in Environmental Engineering, 2024)
This study rigorously assesses emissions from diverse equipment at Dar es Salaam Port, analyzing CO, NOx, SO2, PM10, and POC emissions across various areas. Detailed data collection includes machine specifications, and calculated emission factors that facilitate precise analysis. The research design includes both evaluation of emissions and a strategic phase for optimizing equipment towards reduction. This study employs Mamdani and Sugeno Fuzzy Inference Systems (FIS) to comprehensively analyze emissions from diverse equipment within Dar es Salaam Port. The FIS enhances precision in emission reduction target-setting by considering the intricate parameters, unique to each equipment type. In 2022, the cumulative emissions of CO, NOx, SO2, PM10, and POC amounted to 185,163, 92,908.4, 40,842.4, 8,067.53, and 9,178.614 pounds, respectively, forming a basis for evaluating sustainability initiatives. Strategic interventions are delineated for each equipment type, from advanced technologies for Rubber-Tired Gantry Cranes (RTG) and systematic replacements for Forklifts. Overarching initiatives include regulatory frameworks, alternative fuels, and technology transitions. The FIS models specify emission reduction targets, such as Mamdani proposing a reduction of 12,504.51 pounds of CO from Berthing Tugs, and Sugeno suggesting 3,751.353 pounds. These nuanced recommendations integrate into a strategic roadmap, guiding Dar es Salaam Port towards a sustainable future.